Amiodarone for arrhythmia in patients with Chagas disease: A systematic review and individual patient data meta-analysis. - Cinara Stein; Celina Borges Migliavaca; Verônica Colpani; Priscila Raupp da Rosa; Daniel Sganzerla; Natalia Elis Giordani; Sandro Renê Pinto de Sousa Miguel; Luciane Nascimento Cruz; Carisi Anne Polanczyk; Antonio Luiz P Ribeiro; Maicon Falavigna (Public Library of Science (PLoS), 2018)
BACKGROUND:Chagas disease is a neglected chronic condition caused by Trypanosoma cruzi, with high prevalence and burden in Latin America. Ventricular arrhythmias are common in patients with Chagas cardiomyopathy, and amiodarone has been widely used for this purpose. The aim of our study was to assess the effect of amiodarone in patients with Chagas cardiomyopathy. METHODOLOGY:We searched MEDLINE, Embase and LILACS up to January 2018. Data from randomized and observational studies evaluating amiodarone use in Chagas cardiomyopathy were included. Two reviewers selected the studies, extracted data and assessed risk of bias. Overall quality of evidence was accessed using Grading of Recommendations Assessment, Development and Evaluation (GRADE). PRINCIPAL FINDINGS:We included 9 studies (3 before-after studies, 5 case series and 1 randomized controlled trial). Two studies with a total of 38 patients had the full dataset, allowing individual patient data (IPD) analysis. In 24-hour Holter, amiodarone reduced the number of ventricular tachycardia episodes in 99.9% (95%CI 99.8%-100%), ventricular premature beats in 93.1% (95%CI 82%-97.4%) and the incidence of ventricular couplets in 79% (RR 0.21, 95%CI 0.11-0.39). Studies not included in the IPD analysis showed a reduction of ventricular premature beats (5 studies), ventricular tachycardia (6 studies) and ventricular couplets (1 study). We pooled the incidence of adverse side effects with random effects meta-analysis; amiodarone was associated with corneal microdeposits (61.1%, 95%CI 19.0-91.3, 5 studies), gastrointestinal events (16.1%, 95%CI 6.61-34.2, 3 studies), sinus bradycardia (12.7%, 95%CI 3.71-35.5, 6 studies), dermatological events (10.6%, 95%CI 4.77-21.9, 3 studies) and drug discontinuation (7.68%, 95%CI 4.17-13.7, 5 studies). Quality of evidence ranged from moderate to very low. CONCLUSIONS:Amiodarone is effective in reducing ventricular arrhythmias, but there is no evidence for hard endpoints (sudden death, hospitalization). Although our findings support the use of amiodarone, it is important to balance the potential benefits and harms at the individual level for decision-making.